Assessing water yield by using remote sensing at Sungai Kuantan, Pahang - Nur Hamidah , Abdul Jalal (2012)
This study investigates the potential of the satellite based rainfall estimates data product from Tropical Rainfall Measuring MiiOI (TRMM) sate1lite, knOWn as TRMM 3B43 Version 6. The satellite-based rainfall is used as the main input in the water balance equation to estimate the water-yield at monthly basis from Jul 2005 to Jun 2010. Sungai Kuantan, Pahang which located in east coast region in the Peninsular Malaysia is used as a study area to evaluate the model performance. The rainfall patterns for both data TRMM and JPS during period Jul 2005-Jun 2010 is alniost similar. Pattern of Watef yield at east coast region based on saonal rainfall be investigated. The results are presented in attribute table and graphical forms. The highest monthly water-yield is 721.7 mm during Dec 2005-2006 periods. And the lowest water-yield monthly during Feb 2009-20 10 periods is -96.81 mm. Assessment of the relationship between flow rata data get from JPS, Malaysia and water-yield product at the study area watershed indicates good accurate assessment of coefficient is R 0.65. Public domain data should be practiced in a broader horizon in hydrologic studies in Malaysia to achieve the development of more accurate assessment.